Evaluation of nutritional and functional properties of plantain (Musa paradisiaca L.) and tigernut (Cyperus esculentus L.) flour blends for food formulations - Adegunwa, M.O.; Adelekan, E.O.; Adebowale, A.A.; Bakare, H.A.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2017)
Some individuals are intolerant to gluten of wheat and other cereals like oats, rye and barley used for food formulations and this intolerance seriously impairs intestinal absorption. There is need to develop alternative gluten-free flours for baking and confectioneries. This research therefore aimed at determining the chemical and functional properties of plantain–tiger nut composite flour to be able to explore its potentials in food formulation. The flours made from matured plantains and tiger nuts were blended at the ratio of 100:0, 70:30, 60:40, 50:50, 40:60, 30:70 and 0:100 to make different plantain–tiger nuts flours and these were analysed using standard methods. The results revealed that protein ranged from 4.55 to 6.78/100 g, fat (2.25–32.75/100 g), crude fibre (3.50–6.13/100 g), bulk density (0.81–0.92 g/cm3), swelling power (38.38–2.37/g), Mg (30.65–49.08 mg/100 g), P (3.65–120.65 mg/100 g), K (71.62–212.08 mg/100 g), Vitamin C (3.18–5.30 mg/100 g) and Vitamin A (1.71–51.31 μg/100 g). There were significant differences (p < 0.05) in the pasting profile of the plantain–tiger nut flour blends and in functional properties of composite flour except for bulk density. Addition of tiger nut flour improved the proximate, mineral and vitamin composition of the composite flour and the study concluded that inclusion of tiger nut flour is a good protein, fat, mineral and vitamin supplement for plantain flour.